Implementation of Local Wisdom-Based Contextual Teaching and Learning in Geography Education at Junior and Senior High Schools in Indonesia: A Systematic Literature Review - M Rizqon Al Musafiri; Ahmad Irfan Ilhami (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
This study aims to map the trends, methodological characteristics, and dominant findings in the implementation of Contextual Teaching and Learning (CTL) based on local wisdom in geography education at the junior and senior secondary school levels in Indonesia. A Systematic Literature Review (SLR) approach was employed using the SPIDER framework, with reporting following the PRISMA 2020 guidelines. A total of 32 SINTA-indexed articles were selected through a staged screening process from the Garuda database, Google Scholar, and the SINTA portal, covering the publication period 2015–2025. The analysis results show that 46.9% of the studies employed a Classroom Action Research (CAR) design, with senior secondary school (SMA) predominating (59.4%). The local wisdom most frequently integrated originated from the island of Java (50.0%) and Bali (15.6%), particularly Pranata Mangsa and Subak. The dominant findings include improvements in cognitive learning outcomes (75% of articles; mean N-Gain of 0.62, moderate category), increased student motivation and engagement, and the strengthening of cultural identity and environmental awareness. This study identifies four major gaps, most notably the scarcity of studies in Eastern Indonesia (6.25%), the absence of longitudinal studies, and limitations in measuring non-cognitive variables. These findings provide a landscape map of the research as well as a priority agenda for the development of contextual geography education in Indonesia.